Embraced by eIF3: structural and functional insights into the roles of eIF3 across the translation cycle - Valášek, Leoš Shivaya; Zeman, Jakub; Wagner, Susan; Beznosková, Petra; Pavlíková, Zuzana; Mohammad, Mahabub Pasha; Hronová, Vladislava; Herrmannová, Anna; Hashem, Yaser; Gunišová, Stanislava (Nucleic acids research, 2017)
Protein synthesis is mediated via numerous molecules including the ribosome, mRNA, tRNAs, as well as translation initiation, elongation and release factors. Some of these factors play several roles throughout the entire process to ensure proper assembly of the preinitiation complex on the right mRNA, accurate selection of the initiation codon, errorless production of the encoded polypeptide and its proper termination. Perhaps, the most intriguing of these multitasking factors is the eukaryotic initiation factor eIF3. Recent evidence strongly suggests that this factor, which coordinates the progress of most of the initiation steps, does not come off the initiation complex upon subunit joining, but instead it remains bound to 80S ribosomes and gradually falls off during the first few elongation cycles to: (1) promote resumption of scanning on the same mRNA molecule for reinitiation downstream-in case of translation of upstream ORFs short enough to preserve eIF3 bound; or (2) come back during termination on long ORFs to fine tune its fidelity or, if signaled, promote programmed stop codon readthrough. Here, we unite recent structural views of the eIF3-40S complex and discus all known eIF3 roles to provide a broad picture of the eIF3's impact on translational control in eukaryotic cells.
Keywords: Protein Binding; Saccharomyces cerevisiae Proteins; RNA, Messenger; Protein Biosynthesis; proteosyntéza; Protein Subunits; ribozomy; podjednotky proteinů; molekulární modely; Models, Molecular; vazba proteinů; Ribosomes; Animals; eukaryotický iniciační faktor 3; lidé; konformace proteinů; Humans; zvířata; Saccharomyces cerevisiae - proteiny; Eukaryotic Initiation Factor-3; Protein Conformation; messenger RNA